2018
DOI: 10.1080/21645515.2018.1474315
|View full text |Cite
|
Sign up to set email alerts
|

Is adding maternal vaccination to prevent whooping cough cost-effective in Australia?

Abstract: Pertussis or whooping cough, a highly infectious respiratory infection, causes significant morbidity and mortality in infants. In adolescents and adults, pertussis presents with atypical symptoms often resulting in under-diagnosis and under-reporting, increasing the risk of transmission to more vulnerable groups. Maternal vaccination against pertussis protects mothers and newborns. This evaluation assessed the cost-effectiveness of adding maternal dTpa (reduced antigen diphtheria, Tetanus, acellular pertussis)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…An analysis from the United States found that differences in the reporting probability (or reporting rate as it is usually denominated) implied a change in the decision whether or not to adopt maternal vaccination [8] . In a study from Australia, the reporting rate was the second most important parameter influencing the cost-effectiveness of maternal immunization [47] . When authors assumed that a higher fraction of cases was reported, maternal aP was more cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis from the United States found that differences in the reporting probability (or reporting rate as it is usually denominated) implied a change in the decision whether or not to adopt maternal vaccination [8] . In a study from Australia, the reporting rate was the second most important parameter influencing the cost-effectiveness of maternal immunization [47] . When authors assumed that a higher fraction of cases was reported, maternal aP was more cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…This section is devoted to a comprehensive theoretical analysis of the proposed fractional model (6) where we investigate some key characteristics of the model and show that the model is well-posed for numerical approximations.…”
Section: Theoretical Analysis Of the Proposed Modelmentioning
confidence: 99%
“…Let V (t) satisfy Equation (6). We apply the Atangana-Beleanu fractional integral (4) to both sides of (6) to obtain…”
Section: Theorem 1 ([54]mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, more than 40 countries worldwide have recommendations for Tdap during pregnancy, including advanced countries like the United States, the United Kingdom, and Australia [11,44]. In these countries, the strategy was assessed as cost-effective [45][46][47]. However, such data are lacking for the South and Southeast Asian regions.…”
Section: Maternal Tdap Vaccinationmentioning
confidence: 99%